Selection process in ornamental plant breeding - Bugallo, Veronica Lucia; Facciuto, Gabriela Rosa (Sociedade Brasileira de Floricultura e Plantas Ornamentais (SBFPO), 2023)
The selection is a process in which the best genotypes are chosen according to the desired characteristics for the specific use of the plant. Novelty, health, particular characteristics of each market and, increasingly, the low environmental impact of its production, are valued. One of the most questionable points in the selection of ornamental plants is the fact that beauty is subjective. To reduce subjectivity, breeders have chosen to delimit the selection criteria previously, generating a ranking and assigning values to each of the characters for the new cultivar. The selection criteria and traits to be evaluated depend on the use for which the crop is intended: cut flowers and foliage, pot plants, and landscape plants. In addition, the selection of functional plants (green walls and curtains, green roofs and ecological function plants) have their own criteria.